An opinion survey of ethical concerns in environmental decision-making in Cape Town and Surrounds: the base line of 2002 - Seeliger, Leanne; Hattingh, Johan P. (Stellenbosch University, 2011)
Report done by the Unit for Environmental Ethics, Stellenbosch University.